Influence of Short Cationic Lipopeptides with Fatty Acids of Different Chain Lengths on Bacterial Biofilms Formed on Polystyrene and Hydrogel Surfaces - Malgorzata Anna Paduszynska; Magdalena Maciejewska; Damian Neubauer; Krzysztof Golacki; Magdalena Szymukowicz; Marta Bauer; Wojciech Kamysz (MDPI AG, 2019)
Nowadays, biomaterials are applied in many different branches of medicine. They significantly improve the patients’ comfort and quality of life, but also constitute a significant risk factor for biofilm-associated infections. Currently, intensive research on the development of novel materials resistant to microbial colonization as well as new compounds that are active against biofilms is being carried out. Within this research, antimicrobial peptides (AMPs) and their analogues are being intensively investigated due to their promising antimicrobial activities. The main goal of this study was to synthesize and evaluate the antimicrobial efficacy of short cationic lipopeptides that were designed to imitate the features of AMPs responsible for antimicrobial activities: positive net charge and amphipacity. The positive charge of the molecules results from the presence of basic amino acid residues: arginine and lysine. Amphipacity is provided by the introduction of decanoic, dodecanoic, tetradecanoic, and hexadecanoic acid chains to the molecules. Lipopeptides (C16-KR-NH2, C16-KKK-NH2, C16-KKC-NH2, C16-KGK-NH2, C14-KR-NH2, C14-KKC-NH2, C12-KR-NH2, C12-KKC-NH2, and (C10)2-KKKK-NH2) were synthesized using a novel solid-phase temperature-assisted methodology. The minimum inhibitory concentrations (MICs), minimum biofilm eradication concentrations (MBECs), and minimum biofilm formation inhibitory concentrations (MBFICs) were determined for the following bacterial strains: Staphylococcus aureus ATCC 25923, Staphylococcus epidermidis ATCC 14990, Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 9027, and Proteus mirabilis PCM 543. The biofilms were cultured on two types of surfaces: polystyrene plates (PS) and contact lenses (CL). The lipopeptides exhibited the ability to inhibit the growth of bacteria in a liquid medium as well as on the PS and CL. The compounds also eliminated the bacterial biofilm from the surface of both materials. In general, the activity against gram-positive bacteria was stronger in comparison to that against gram-negative strains. There were certain discrepancies between the activity of compounds against the biofilm cultured on PS and CL. This was especially noticeable for staphylococci—the lipopeptides presented much higher activity against biofilm formed on the PS surface. It is worth noting that the obtained MBEC values for lipopeptides were usually only a few times higher than the MICs. The results of the performed experiments suggest that further studies on lipopeptides and their potential application in the treatment and prophylaxis of biofilm-associated infections should be conducted.